System Integration of Law of the Eurasian Еconomic Union - Z. T. Iskakova (Евразийская интеграция: экономика, право, политика, 2019)
This article is dedicated to evaluation of theoretical understanding of the EAEU integration law, the allocation of the right of integration associations in an independent legal system, with specific legal character and nature.